Analysis of Potential Perma Number 1 Year 2013 on Assets Outside the Account Without Punishment - Adria Fathan Mahmuda; Akiko Ivana; Tiara (JUSTICES: Journal of Law, 2024)
The Law number 14 of 1970 jo. The Law number 48 of 2009 on Judicial Power mandates that the Supreme Court as the organizer of judicial power has the right to issue implementing regulations, namely Supreme Court Regulations (Perma) in order to support the performance of the Supreme Court itself. This then became the basis for the establishment of Perma No. 1 of 2013 concerning Procedures for Settling Applications for Handling Assets in ML or Other Crimes as Procedural Law for handling assets resulting from ML that are In Rem Forfeiture or the origin of the owner is unknown. However, viewed hierarchically, the legal vacuum in the Procedural Law for the procedure of handling assets from ML is too broad to be regulated only in the Perma instrument. Furthermore, this Perma has a much broader indication to regulate the problem of assets of ML/TF proceeds that are outside the account and specify asset tracing efforts on assets of ML/TF proceeds outside the account. This possibility and opportunity is what this paper intends to explore through two problem formulations, namely how the jurisdiction of Perma Number 1 of 2013, its implementation, and efforts to implement asset tracing of assets outside the account in accordance with the mandate of Perma Number 1 of 2013. The research method we use is the normative juridical method and is qualitative in nature with a conceptual, case, and statute approach.